2013
DOI: 10.1182/blood-2012-09-454355
|View full text |Cite
|
Sign up to set email alerts
|

MYD88 L265P in Waldenström macroglobulinemia, immunoglobulin M monoclonal gammopathy, and other B-cell lymphoproliferative disorders using conventional and quantitative allele-specific polymerase chain reaction

Abstract: Key Points• MYD88 L265P is expressed in WM and IgM MGUS patients using AS-PCR assays with potential use in diagnostic discrimination and response assessment.By whole-genome and/or Sanger sequencing, we recently identified a somatic mutation (MYD88 L265P) that stimulates nuclear factor kB activity and is present in >90% of Waldenström macroglobulinemia (WM) patients. MYD88 L265P was absent in 90% of immunoglobulin M (IgM) monoclonal gammopathy of undetermined significance (MGUS) patients. We therefore developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
364
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 363 publications
(384 citation statements)
references
References 27 publications
15
364
1
4
Order By: Relevance
“…12,15,22,23 In contrast, this abnormality has been found much less frequently in other small B-cell neoplasms, including 4-21% of cases diagnosed as splenic marginal zone lymphoma and 1-10% of chronic lymphocytic leukemia. 11,12,15,[23][24][25][26] The current study was designed to examine the morphologic correlates of MYD88 L265P in nodal and splenic small B-cell neoplasms with plasmacytic differentiation, and determine whether molecular studies for this mutation may assist in the diagnosis of lymphoplasmacytic lymphoma in routine practice. Figure 3 Four cases with MYD88 mutation (two originally classified as nodal marginal zone lymphoma with plasmacytic differentiation and two as small B-cell neoplasm with plasmacytic differentiation, not otherwise specified) showed similar features.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…12,15,22,23 In contrast, this abnormality has been found much less frequently in other small B-cell neoplasms, including 4-21% of cases diagnosed as splenic marginal zone lymphoma and 1-10% of chronic lymphocytic leukemia. 11,12,15,[23][24][25][26] The current study was designed to examine the morphologic correlates of MYD88 L265P in nodal and splenic small B-cell neoplasms with plasmacytic differentiation, and determine whether molecular studies for this mutation may assist in the diagnosis of lymphoplasmacytic lymphoma in routine practice. Figure 3 Four cases with MYD88 mutation (two originally classified as nodal marginal zone lymphoma with plasmacytic differentiation and two as small B-cell neoplasm with plasmacytic differentiation, not otherwise specified) showed similar features.…”
Section: Discussionmentioning
confidence: 98%
“…19,20 Subsequent studies from multiple institutions have confirmed MYD88 L265P to be present in the majority of lymphoplasmacytic lymphoma/ Waldenstrom's macroglobulinemia, with reported incidence from 67 to 93%. 12,15,21 The mutation has also been found in 44-87% of IgM monoclonal gammopathy of undetermined significance. 12,15,22,23 In contrast, this abnormality has been found much less frequently in other small B-cell neoplasms, including 4-21% of cases diagnosed as splenic marginal zone lymphoma and 1-10% of chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations